ANTIBACTERIAL ACTIVITY TEST OF TEA TREE AND LEMON OIL COMBINATION AND ITS FORMULATION IN CREAM PREPARATION - Sulistiorini Indriaty; Rima Yulia Senja; Deni Firmansyah; Nur Rahmi Hidayati; Nina Karlina; Muhammad Yani Zam Zam; Dhea Aulia Ramadhani (Medical Sains : Jurnal Ilmiah Kefarmasian, 2024)
Tea tree oil contains hydrocarbon compounds, namely terpenes, especially monoterpenes, sesquiterpenes, and alcohols. Terpinen-4-ol is the main component of tea tree oil, which has antimicrobial activity. Lemon oil is useful as an antibacterial because it contains flavonoids that prevent attacks from pathogenic bacteria. This study aims to determine whether tea tree and lemon oil have antibacterial activity against Propionibacterium acnes bacteria and can be formulated into cream preparations. The antibacterial activity test of the combination of tea tree oil and lemon oil in the 1: 1, 1: 2, and 2: 1 ratio was carried out in vitro against Propionibacterium acnes bacteria by disc diffusion method and using virile gel as a positive control. The cream stability test is replicated using the cycling test method with organoleptic test parameters, homogeneity, pH, dispersion, cream type testing, viscosity, and flow properties. The stability test results with the cycling test method showed good stability results, including organoleptic tests, homogeneity, spreadability, pH, emulsion type, viscosity, and flow properties. The combination of tea tree and lemon essential oils in a 1:1, 1:2, 2:1 ratio has antibacterial activity against Propionibacterium acnes bacteria with inhibition zones diameter ±1,23 cm, ±1,12 cm, and ±1,12 cm and control has ±1,53 cm. Combining tea tree and lemon essential oil in a 1:1, 1:2, and 2:1 ratio has antibacterial activity against Propionibacterium acnes bacteria and can be formulated into cream preparations. Keywords: tea tree oil, lemon oil, antibacterial, Propionibacterium acnes, cream.